A Constitution for All Times - Pamela S. Karlan (The MIT Press, 2013)
In his 1928 book The Paradoxes of Legal Science, then-judge, and later Supreme Court justice, Benjamin Cardozo wrote that rather than defining â€œdue process of lawâ€â€”a critical concept in constitutional lawâ€”courts â€œleave it to be â€˜pricked outâ€™ by a process of inclusion and exclusion in individual cases. . . . It is all very well to go on pricking the lines,â€ he observed, â€œbut the time must come when we shall do prudently to look them over, and see whether they make a pattern or a medley of scraps and patches.â€ This book originated as a series of columns in Boston Review written between 2010 and 2013. Some of the columns addressed individual cases then pending before or recently decided by the Supreme Court.Others covered broader questions of interpretive method or the Courtâ€™s role as an institution. But taken together, they go beyond pricking the lines to lay out a coherent approach to thinking about constitutional law and the Courtâ€™s role in our democracy